A novel, low-cost and robust method for determining molten salt density at high temperatures. (September 2021) - Severino, John; Jacob, Rhys; Belusko, Martin; Liu, Ming; Bruno, Frank
Highlights: A methodology for high temperature pycnometric density measurement was developed. An in-house apparatus was constructed to measure the density of molten salts. The apparatus was calibrated using sodium chloride with an error of ±0.6%. The density of 5 molten salts were measured up to 900 °C. Abstract: A pycnometric method was utilised to determine the liquid density of carbonate and/or chloride salts at high temperatures. When compared to alternative methods, the measurements were quick and repeatable using common laboratory equipment. The methodology was validated using sodium chloride as a reference material with an error of ±0.6% when compared to other literature sources. Overall, the absolute measurement error was found to lead to a ±0.3% uncertainty for the measured values where the maximum error was due to the determination of the meniscus volume. This methodology was then used to study the liquid density of several other promising molten salts (32.1:33.4:34.5 wt% Li2 Na2 K2 -CO3, 41.57:25.43:33.0 wt% Na2 CO3 :NaCl:KCl, 59.45:40.55 wt% Na2 CO3 :NaCl, 47.19:52.81 wt% Na2 K2 -CO3 ) and found to have good agreement when compared to other studies and methodologies (±7.6% from predicted). In all cases it was found that the liquid density decreased linearly from the melting point.